Recognition and inequalities in older adults' sexuality in Chile - Gómez-Urrutia, Verónica; Gartenlaub, Andrea; Tello-Navarro, Felipe (Frontiers in Sociology, 2024)
This paper explores older adults' perceptions on sexuality and affectivity in Chile, according to class and sex. The study is based on computer-assisted telephonic interviews with people aged 60 and over, men and women (N=481). Data were analyzed using chi-squared tests and binary logistic regressions. Results show that maintaining an active sex life is important for both sexes, contradicting the commonsense view according to which the relevance allocated to sex decreases significantly with age. However, the data show significant differences in perceptions by sex, suggesting that gendered conceptions regarding sexuality are influential along the entire life cycle. There are also relevant differences according to class, revealing the inequalities present in the expression of sexuality in Chile.